Physics of new methods of charged particle acceleration - Bonch-Osmolovsky, A. G (World Scientific, 1994)
Includes bibliographical references.; Ch. 1. Introduction. Historical Review -- Ch. 2. Some Quasistatic Effects of Space Charge (collective Effects) in the Charge Particle Ensembles -- Ch. 3. The Foundation of the Physics and Schemes of Collective and Coherent Methods of Acceleration. Veksler Problem, Impact Method of Acceleration -- Ch. 4. The Problems of Equilibrium of Relativistic Electron Rings -- Ch. 5. On a Stability of Electron Rings -- Ch. 6. Beam-Wave Collective Methods of Acceleration. The Physics of Resonance Doppler Interaction, its Mathematic Description -- Supplement: Proper (Noninertial) Systems of Coordinates.